Enrichment and recovery of a Malaysian reservoir - Arumugam, P. T.; Furtado, J. I. (Springer, 1980)
Subang reservoir was originally oligotrophic. Due to continuous heavy nutrient loading, especially of N, P, K and organic matter from a nearby polluted auxiliary riverine intake source, the reservoir becomes progressively eutrophic. An increase in the total ionic content and a decrease in NO3 occurs, while PO4 and NH3 content fluctuates. A marked successional change in the phytoplankton composition occurs favouring blooms of undesirable algal species viz. Microcystis aeruginosa, and in later stages of the floating macrophyte, Salvinia molesta. On stoppage of the auxiliary intake water, the reservoir gradually becomes soft and acidic. A decrease in the PO4 and NH3 content occurs, while NO3 fluctuates. A somewhat reverse succession al change occurs favouring Staurastrum spp., more characteristic of Malaysian soft, acidic waters.